Articulate Storyline-based interactive media: An ADDIE-model development for algebraic operation learning - Arifin, Sujinal; Efriani, Arvin; Umayah, Sarifatul (Universitas Negeri Yogyakarta, 2026)
Students' difficulties in understanding algebraic operations, particularly in translating contextual problems into symbolic expressions, highlight the need for instructional media that support visualisation, structured scaffolding, and active engagement. This study aimed to develop and evaluate Articulate Storyline-based interactive media for learning algebraic operations using the ADDIE model (analysis, design, development, implementation, and evaluation). Data were collected through expert validation sheets, student practicality questionnaires, and post-test assessments, and analysed using descriptive statistical techniques (mean scores and percentage distributions). The product was implemented in three stages: one-to-one testing (3 students), small-group testing (8 students), and a field trial involving 18 seventh-grade students. Expert validation indicated that the media was highly valid across content accuracy, contextual suitability, presentation quality, and instructional design. Practical results showed positive student responses regarding usability and engagement. The post-test mean score was 82, and all students achieved medium to very high performance, indicating potential improvement in conceptual understanding. This study contributes to mathematics education by providing an empirically validated multimedia design that integrates contextual animation, step-by-step symbolic visualisation, and interactive feedback to address abstraction challenges in algebra learning.